2023
DOI: 10.1101/2023.08.21.23294253
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcobalamin Receptor Autoantibodies in Central Vitamin B12 Deficiency

John V. Pluvinage,
Thomas Ngo,
Christopher M. Bartley
et al.

Abstract: Vitamin B12 is critical for hematopoiesis and myelination.1Deficiency can cause neurologic deficits including loss of coordination, spasticity, and cognitive decline.2,3,4However, diagnosis relies on vitamin B12 measurement in the blood which may not accurately reflect levels in the brain. Here, we discovered an autoimmune cause of vitamin B12 deficiency restricted to the central nervous system (CNS), termed autoimmune B12 central deficiency (ABCD). Using programmable phage display, we identified an autoantibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…80,81 An intriguing recent study has demonstrated that (auto)antibodies against the CD320 (transcobalamin) receptor may interfere with the proper uptake of cobalamin into the brain. 82 Long-term studies clearly indicate that treatment with pharmacological doses of B12 and the corresponding increase in serum B12 concentrations do not increase mortality risk. 83 Treatment with parenteral B12 during pregnancy and lactation is safe, and should not be postponed or stopped.…”
Section: Monitoring Outcome and Follow-upmentioning
confidence: 99%
“…80,81 An intriguing recent study has demonstrated that (auto)antibodies against the CD320 (transcobalamin) receptor may interfere with the proper uptake of cobalamin into the brain. 82 Long-term studies clearly indicate that treatment with pharmacological doses of B12 and the corresponding increase in serum B12 concentrations do not increase mortality risk. 83 Treatment with parenteral B12 during pregnancy and lactation is safe, and should not be postponed or stopped.…”
Section: Monitoring Outcome and Follow-upmentioning
confidence: 99%